Kombinasi Jus Tomat dan Jeruk Meningkatkan Kadar Hemoglobin Pada Ibu Hamil Anemia Ringan - Wardani, Oktoviani Trisunu; Asih, Fransisca Retno; Sholihin, Sholihin (POLTEKKES KEMENKES MANADO, 2023)
Background: Anemia during pregnancy continues to become national and global, although program supplementation substance iron has already been held. Tomatoes and oranges contain substances iron and vitamin C, beneficial as complementary alternative medicine for anemia moment pregnant. Objective: To know the influence combination you tomato and orange on the enhancement much hemoglobin on a mother pregnant. Method: Research using design quasi-experiment with approach pretest-posttest nonequivalent control group design on 60 pregnant women (30 subjects per group) who came sequentially to the Sumberagung Community Health Center from January to March 2022 and had passed the inclusion criteria (gestational age 16-36 weeks, mild anemia with hemoglobin levels of 1010.9 gr/dl, and willing to be research subjects) and exclusion (inpartum, having complications, and blood disorders). Research subjects in the intervention group were given a combination of tomato (150 grams) and orange (100 grams) juice every day after 15 minutes of iron supplementation for seven days. Hemoglobin levels were measured before and after the intervention. Data analysis using tests mann Whitney and Wilcoxon because the data is not normally distributed with SPSS version 22. Results: research shows that giving a combination of tomato juice after iron supplementation increases hemoglobin levels in pregnant women (p<0.000), but is not significantly different compared to iron supplementation alone (p>0.000).